2014
DOI: 10.1080/19338244.2013.845138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Forearm Support on Upper Body for People in Front of Monitor: A Meta-Analysis

Abstract: With the ever-growing number of people who work at visual display terminals, the work-related musculoskeletal disorders of the upper body are believed to be an important problem all over the world. The forearm support, which can keep the forearm and wrist in biomechanical posture, is a possible protective factor of the development of upper body syndrome. This meta-analysis examines the efficacy of forearm support in reducing upper body syndrome. The Cochrane Library, EMBASE, Ovid, ScienceDirect, SpringerLink, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several studies evaluated muscle activity in forearm and wrist support during typing and mouse tasks. However, among the identified studies there is still divergence about the effect of the forearm support15, 16, 20,21,22,23,24,25,26,27 ) and about the recommendation for safe limits for the shoulder posture28,29,30 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluated muscle activity in forearm and wrist support during typing and mouse tasks. However, among the identified studies there is still divergence about the effect of the forearm support15, 16, 20,21,22,23,24,25,26,27 ) and about the recommendation for safe limits for the shoulder posture28,29,30 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis about the effect of forearm support in reducing upper body disorders showed that forearm support had statistically significant effect on preventing upper limb disorders27 ) . However, this conclusion was based on only four studies, and none of them controlled for the shoulder posture in a supported condition.…”
Section: Introductionmentioning
confidence: 99%